Role of the retrograde Carlino technique for chronic total occlusion percutaneous coronary intervention. Issue 3 (22nd January 2023) - Azzalini, Lorenzo; Boudou, Nicolas; Avran, Alexandre; Kane, Jesse; Lombardi, William L.; Kearney, Kathleen E.; Carlino, Mauro
Abstract: Background: There is scarce data on the outcomes of the Carlino technique for chronic total occlusion (CTO) percutaneous coronary intervention (PCI). We aimed to investigate the indications and outcomes of the Carlino technique as performed in the context of the retrograde approach. Methods: We pooled CTO PCI cases where a retrograde Carlino technique was performed from high‐volume operators at four centers. The Carlino technique was characterized according to its indication (achieving plaque/cap modification, clarifying microcatheter location within the vessel, resolving distal cap ambiguity) and was considered successful when it led to the desired outcome. Results: A total of 43 patients were included. Occlusion complexity was very high (mean J‐CTO score 3.3 ± 0.8). The two most common indications were understanding the anatomy of the occlusion and clarifying gear location (37.2%) and impenetrable distal cap (34.9%). The Carlino technique was successful in 88.4% of cases. Overall technical and procedural success was 86.0%. The most common successful crossing technique was reverse controlled antegrade and retrograde subintimal tracking (70.3%). No complications were attributed to the Carlino technique. Conclusions: We observed a high success rate of the retrograde Carlino technique, as well as overall technical and procedural success rates. No Carlino technique‐related complications were observed. Additional data from larger registries are warranted to further confirm the safety and efficacy of this technique.